1970
DOI: 10.1002/ajpa.1330320112
|View full text |Cite
|
Sign up to set email alerts
|

On deflecting wrinkles and the Dryopithecus pattern in human mandibular molars

Abstract: The utility of the traditional Dryopithecus pattern observations on mandibular molars in hominid dental analysis has been challenged recently from several points of view. Both fossil and contemporary evidence suggest the independence of cusp number and groove pattern on mandibular molars and the quality of dentitions which are normally available for study make it difficult to determine both aspects of pattern (cusp number, groove pattern) equally. Now this paper shows that one of the polymorphisms on the occlu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

1971
1971
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…However, the incidence of Y-groove may be spurious. Morris (1969) has previously shown that both deflecting wrinkle and Y-groove involve contact between cusps 2 (metaconid) and 3 (hypoconid), so that a molar with a deflecting wrinkle is also recorded as having Y-groove. In this study, 26.3% of the San dentitions that contain Y-groove also have some expression of deflecting wrinkle.…”
Section: Resultsmentioning
confidence: 99%
“…However, the incidence of Y-groove may be spurious. Morris (1969) has previously shown that both deflecting wrinkle and Y-groove involve contact between cusps 2 (metaconid) and 3 (hypoconid), so that a molar with a deflecting wrinkle is also recorded as having Y-groove. In this study, 26.3% of the San dentitions that contain Y-groove also have some expression of deflecting wrinkle.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have noted difficulty in scoring traits due to wear (Morris, 1970;Nichol and Turner, 1986;Wu and Turner, 1993), including MxPAR (Scott, 1973). A detailed analysis of the effect of dental wear on MxPAR by the senior author (Burnett, 1998) suggests that the degree of wear influences sample frequencies so that trait frequency decreases as wear increases.…”
Section: Scoringmentioning
confidence: 99%
“…When the ridge is deflected, it is referred to as the deflecting wrinkle (Weidenreich, 1945;Morris, 1970). This is the only variable that was classified into absence or presence categories without ranking the degree of trait expression.…”
Section: Trait Classificationsmentioning
confidence: 99%